2007
DOI: 10.1002/pssc.200675774
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lattice defects in Cu thin films by positron annihilation spectroscopy

Abstract: Positron lifetime measurements have been performed for Cu thin films in order to identify lattice defects. Theoretical positron lifetimes of vacancy clusters of Cu are also calculated for identification of the experimental values. Cu thin films were prepared by electro chemical deposition (ECD) and physical vapour deposition (PVD). All of the Cu thin films have longer positron lifetimes than bulk Cu does. This indicates that lattice defects are introduced during deposition. However composition analysis of posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…The positron lifetime for this sample was 111 ps. This value agreed with the reported lifetime of positrons that are delocalized and annihilated in interstitial sites [3]. This indicates that the S value of the annealed bulk-Cu sample, observed at E = 25 -30 keV, was the characteristic value of S for a Cu perfect crystal.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The positron lifetime for this sample was 111 ps. This value agreed with the reported lifetime of positrons that are delocalized and annihilated in interstitial sites [3]. This indicates that the S value of the annealed bulk-Cu sample, observed at E = 25 -30 keV, was the characteristic value of S for a Cu perfect crystal.…”
Section: Resultssupporting
confidence: 89%
“…This means that the S value in this energy range corresponds to the annihilation of positrons in the 1 µm pure-Cu film. A previous study on conventional positron annihilation lifetime spectroscopy indicated that almost all positrons which were implanted into a PVD-pure-Cu film were trapped at grain boundaries and annihilated there because of submicron grain sizes [3]. This was the reason for the higher value of S for a pure-Cu film compared to the value of a Cu perfect crystal.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…From these considerations, it is concluded that the defect component of s d1 is due to dislocations or grain boundaries. 38 From these results, we can say that the reflow behavior of Cu films is accelerated by the presence of vacancies or dislocations, which are present in large numbers compared with equilibrium point defects in as-deposited Cu films. The Cu films are embedded in the vias and trenches by the abrupt migration of vacancies or dislocations during isochronal annealing above 250°C.…”
Section: Positron Annihilation Study Of Lattice Defects In Cu Filmsmentioning
confidence: 91%